Identification and survival outcomes of a cohort of patients with cancer of unknown primary in Ontario, Canada. (26th November 2015) - Kim, Chong S.; Hannouf, Malek B.; Sarma, Sisira; Rodrigues, George B.; Rogan, Peter K.; Mahmud, Salaheddin M.; Winquist, Eric; Brackstone, Muriel; Zaric, Gregory S.
Abstract : Background. Cancer of unknown primary origin (CUP) is defined by the presence of pathologically identified metastatic disease without clinical or radiological evidence of a primary tumour. Our objective was to identify incident cases of CUP in Ontario, Canada, and determine the influence of histology and sites of metastases on overall survival (OS). Material and methods. We used the Ontario Cancer Registry (OCR) and the Same-Day Surgery and Discharge Abstract Database (SDS/DAD) to identify patients diagnosed with CUP in Ontario between 1 January 2000, and 31 December 2005. Patient diagnostic information, including histology and survival data, was obtained from the OCR. We cross-validated CUP diagnosis and obtained additional information about metastasis through data linkage with the SDS/DAD database. OS was assessed using Cox regression models adjusting for histology and sites of metastases. Results. We identified 3564 patients diagnosed with CUP. Patients without histologically confirmed disease (n = 1821) had a one-year OS of 10.9%, whereas patients with confirmed histology (n = 1743) had a one-year OS of 15.6%. The most common metastatic sites were in the respiratory or digestive systems (n = 1603), and the most common histology was adenocarcinoma (n = 939). Three-year survival rates were 3.5%, 5.3%, 41.6% and 3.6% among adenocarcinoma, unspecified carcinoma, squamous cell carcinoma and undifferentiated histology, respectively. Three-year survival rates were 40%, 2.4%, 8.0% and 4.6% among patients with metastases localised to lymph nodes, the respiratory or digestive systems, other specified sites, and unspecified sites, respectively. Conclusion. CUP patients in Ontario have a poor prognosis. Some subgroups may have better survival rates, such as patients with metastases localised to lymph nodes and patients with squamous cell histology.